Pengaruh Model Pembelajaran Problem Based Learning Terhadap Kemampuan Berpikir Kritis dan Hasil Belajar Siswa Kelas X OTKP di SMK Negeri 2 Tuban - Dyah Nur Sholicha; Siti Sri Wulandari (Jurnal Pendidikan Administrasi Perkantoran (JPAP), 2020)
AbstractThis study purpose to analyze the effect of the Problem Based Learning teaching model on critical thinking skills and student learning outcomes and describe the implementation of Problem Based Learning basic competencies applying the maintenance procedures of the Xth Grade OTKP archive in the Vocational High School 2 Tuban. This type of experimental research with the Quasi Experiment approach. The population used in all class X OTKP in SMK Negeri 2 Tuban, the sample used two classes including class X OTKP 2, which was a total experiment of 36 students, along with class X OTKP 4, which was a total control of 36 students. Data analysis techniques used homogeneity testing, normality testing, as well as t-test and gain score with SPSS aided 22. The results showed that: 1) The Problem Based Learning teaching model had a significant effect on increasing the critical thinking skills of Grade X OTKP students in SMK Negeri 2 Tuban; 2) The Problem Based Learning teaching model has a significant effect on improving student learning outcomes in class X OTKP at SMK Negeri 2 Tuban; 3) Implementation of the Problem Based Learning teaching model is carried out in accordance with the teaching tools in the form of a Learning Implementation Plan (RPP).Keywords : Critical thinking skill; Learning  outcomes; Problem based learning